Identification, Sequencing and Genetic Diversity of Zucchini Tigre Mosaic Virus Infecting Cucurbita Species in Argentina - Brugo Carivali, María Florencia (2025)
Cucurbit crops are constantly threatened by viral diseases. In Argentina, five potyviruses have been identified, including the recently discovered zucchini tigre mosaic virus (ZTMV). This study aimed to evaluate the molecular epidemiology of ZTMV. The virus was identified and characterised using molecular techniques including reverse transcription-PCR, Sanger sequencing and Oxford Nanopore sequencing. Eighteen coat protein (CP) sequences and one complete genome sequence were obtained. Phylogenetically, the new Argentine isolates formed their own clade separated from all other ZTMV isolates. Population genetic analyses of CP sequences revealed high haplotype diversity and moderate-to-high nucleotide diversity across phylogroups. This region was under a strong negative selection. Neutrality tests were not statistically significant. The genetic differentiation parameters were statistically significant, indicating that ZTMV phylogenetic groups were different and supporting the proposed novel structure. Moreover, an infrequent gene flow between populations was observed. Haplotype analysis of 63 CP sequences revealed 54 distinct haplotypes, 15 of which originated from Argentina with a high number of mutations between clusters. The network grouped the haplotypes in the same clusters as those observed in the phylogenetic tree. One event of intraspecific recombination was found, which encompassed P1 and HC-Pro coding regions. The results obtained suggest that Argentine ZTMV populations have developed an evolutionary strategy characterised by low genetic diversity, low mutation rates and intraspecific recombination. All these strategies contribute to the virus adaptation to survival in new environments and hosts.